PENINGKATAN HASIL BELAJAR PENJUMLAHAN BILANGAN BULAT DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION DI KELAS V SDN 26 TELUK BAYUR PADANG - Wahyuni, Nova Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research backed by sum of integers learning in elementary school still use teacher center, consequently the result of the study is still low. Purpose of the research is to describe improving the student outcomes in sum of integers learing by used RME strategy at fifth grade in SD N 26 Teluk Bayur Padang. Kind of this research is an action research with quantitative and qualitative approach. The result of this research showed that, the student outcomes in cycle I was 74 and this increased to 80 in cycle II. From the result it can be concluded that strategy RME can increase the students outcomes in sum of integers learing at fifth grade SD N 26 Teluk Bayur Padang.   Kata Kunci : hasil belajar penjumlahan bilangan bulat; realistic mathematics education: RME